Preparation of electrochemically active silicon nanotubes in highly ordered arrays - Gruenzel, Tobias; Lee, Young Joo; Kuepper, Karsten; Bachmann, Julien (Beilstein Journal of Nanotechnology, 2013)
Silicon as the negative electrode material of lithium ion batteries has a very large capacity, the exploitation of which is impeded by the volume changes taking place upon electrochemical cycling. A Si electrode displaying a controlled porosity could circumvent the difficulty. In this perspective, we present a preparative method that yields ordered arrays of electrochemically competent silicon nanotubes. The method is based on the atomic layer deposition of silicon dioxide onto the pore walls of an anodic alumina template, followed by a thermal reduction with lithium vapor. This thermal reduction is quantitative, homogeneous over macroscopic samples, and it yields amorphous silicon and lithium oxide, at the exclusion of any lithium silicides. The reaction is characterized by spectroscopic ellipsometry for thin silica films, and by nuclear magnetic resonance and X-ray photoelectron spectroscopy for nanoporous samples. After removal of the lithium oxide byproduct, the silicon nanotubes can be contacted electrically. In a lithium ion electrolyte, they then display the electrochemical waves also observed for other bulk or nanostructured silicon systems. The method established here paves the way for systematic investigations of how the electrochemical properties (capacity, charge/discharge rates, cyclability) of nanoporous silicon negative lithium ion battery electrode materials depend on the geometry.
Keywords: atomic layer deposition; electrochemistry; lithium ion battery electrode; silica thermal reduction; silicon nanotubes